Ekologi Sastra pada Puisi "Syair Orang Lapar" Karya Taufiq Ismail - Alya, Dina Fitri; Ajija, Susan Nur; Rahayu, Sri (Literature Research Journal, 2023)
This study aims to describe the social impact of the poem "Syair Orang Hungry" by Taufiq Ismail with a literary ecology approach. The method used is a qualitative descriptive method with an ecological literature approach. Literary ecology is a way of understanding environmental issues from a literary perspective or vice versa, how to understand literature from an environmental perspective. The object of this study is a poem entitled "Syair Orang Hungry" by Taufiq Ismail. Poetry is a form of literary work created by poets by utilizing various things as inspiration originating from the poet's experience and the poet's expressions that are being felt. The results of the study show that the poem "Syair Orang Hungry" by Taufiq Ismail describes the social impacts that occur on the local population. There are several social impacts, namely 1) unpreparedness to face drought; 2) lack of alcohol in lament; 3) the consequences of natural disasters.Tujuan penelitian ini untuk menggambarkan dampak sosial yang terukir dalam puisi â€œSyair Orang Laparâ€ karya Taufiq Ismail dengan pendekatan ekologi sastra. Penelitian ini mengaplikasikan metode deskriptif kualitatif dengan pendekatan ekologi sastra. Ekologi sastra diartikan sebagai cara seseorang menanggapi problematika di lingkungan dalam sudut pandang sastra. Objek dalam penelitian ini adalah puisi yang berjudul â€œSyair Orang Laparâ€ karya Taufiq Ismail. Puisi diartikan sebagai bentuk karya sastra yang disusun oleh penyair dengan memanfaatkan beragam hal sebagai inspirasi yang berasal dari pengalaman penyair dan ekspresi penyair yang sedang dirasakan. Hasil penelitian menunjukkan bahwa puisi â€œSyair Orang Laparâ€ karya Taufiq Ismail menggambarkan dampak sosial yang terjadi pada penduduk setempat. Terdapat beberapa dampak sosial, yakni 1) ketidaksiapan menghadapi kemarau; 2) minimnya dalam menyuarakan keluh kesah; 3) konsekuensi bencana alam.